2015
DOI: 10.1007/s12011-015-0316-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Selenomethionine Supplementation on Growth Performance, Tissue Se Concentration, and Blood Glutathione Peroxidase Activity in Kid Boer Goats

Abstract: We used 240 kid Boer goats that were divided into six groups. The control group was fed a basal diet containing 0.05 mg of selenium (Se)/kg dry matter (DM). Trial groups received the basal diet supplemented with 0.1, 0.2, 0.3, 0.4, or 0.5 mg Se/kg DM (using a commercial selenomethionine product). Trial groups showed an improvement in growth performance (P < 0.05) despite no change in average daily feed intakes (ADFIs) (P > 0.05) compared to the control group A, quadratic model showed a correlation between glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The findings of this experiment are in line with the previous report where Vit E and Se increased blood plasma concentration of Se in goats reared in selenium-deficient soil [ 14 ]. Our results are in agreement with the previous studies in which combination of Vit E and Se increased the level of plasma Se and improved the reproductive performance in goats [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this experiment are in line with the previous report where Vit E and Se increased blood plasma concentration of Se in goats reared in selenium-deficient soil [ 14 ]. Our results are in agreement with the previous studies in which combination of Vit E and Se increased the level of plasma Se and improved the reproductive performance in goats [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…SeMet has been utilized for Se supplementation in many clinical trials, and other organic Se species, such as MeSeCys, have also been demonstrated to be suitable for Se supplementation (Čadková et al., 2018). Supplementation with SeMet improved growth performance, Se concentrations in tissue, and blood glutathione peroxidase activity in kid Boer goats (Song et al., 2015). SeMet supplementation significantly reduced aortic atherosclerotic plaque formation, improved vessel function, and decreased the inflammatory response in high fat diet fed apolipoprotein E deficient (ApoE –/– ) mice, highlighting the potential of SeMet supplementation in atherosclerosis therapy (Zhang et al., 2020).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%
“…Selenium is involved in growth and development, as well as taking part in the regulation processes related with production [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ], and reproduction abilities of animals [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%